2022
DOI: 10.1155/2022/1784572
|View full text |Cite
|
Sign up to set email alerts
|

Thickness of the Deltoid Muscle and Location of the Anterior Branch of the Axillary Nerve and the Posterior Circumflex Humeral Artery for Deltoid Injections

Abstract: This study investigated the thickness of the deltoid muscle and the location of the anterior branch of the axillary nerve (AAN) and posterior circumflex humeral artery (PCHA), with the goal of maximizing the effectiveness of deltoid injections. Forty specimens from 22 adult Korean cadavers were used. A reference line was identified, connecting the anterior point of the deltoid muscle (AP) and the posterior point of the deltoid muscle (PP) on the surface. The midpoint between the AP and PP was used as the origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Ye-Gyung Kim et al (Korea) and Nicholson et al (USA) reported significant difference in the length of the acromion between males and females. Our results agree with those of these two studies [8,15]. Nakatani et al (Japan) in their study observed that AXN is frequently positioned 5 cm below the mid-acromion point [16].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Ye-Gyung Kim et al (Korea) and Nicholson et al (USA) reported significant difference in the length of the acromion between males and females. Our results agree with those of these two studies [8,15]. Nakatani et al (Japan) in their study observed that AXN is frequently positioned 5 cm below the mid-acromion point [16].…”
Section: Discussionsupporting
confidence: 93%
“…Two investigators conducted the measurements separately on each cadaver at different times in the day. A research study piloted by Ye-Gyung Kim et al (2022) in Korean population was referred to as reference study for the landmarks used for conducting anthropometric measurements in the present study [8]. Before taking the measurements, bony landmarks were identified and marked using specimen marking pins on the concerned region namely the anterior point of the lateral border of acromion (AP), the posterior point of the lateral border of acromion (PP), and the acromion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation